Aberrant brain-expressed X-linked 4 (BEX4) expression is a novel prognostic biomarker in gastric cancer. Issue 47 (20th November 2020) - Zhu, Chenhong; Xiao, Deshuang
Abstract: Background: This study aimed to investigate the expression level of X-linked 4 (BEX4) in patients with gastric cancer (GC) and to investigate the prognostic significance of BEX4. Methods: The mRNA expression of BEX4 was analyzed using the Cancer Genome Atlas (TCGA) datasets. The relationship between the expression of BEX4 and GC patient survival was assessed using a Kaplan-Meier plot and Log Rank test. Multivariate cox regression analysis was used to evaluate prognostic factor. The diagnostic value of BEX4 expression in GC tissue was determined through receiver operating characteristic (ROC) curve analysis. Gene set enrichment analysis (GSEA) was used to explore BEX-4 related signaling pathways in GC. Furthermore, the Human Protein Atlas (HPA) database and GSE62254 dataset were used for further validation. Results: BEX4 was expressed at lower level in GC tissues than normal gastric tissues. The lower expression of BEX4 was also validated at protein level in HPA database. The area under the ROC curve for BEX4 expression in normal gastric tissue and GC was 0.791, which presented modest diagnostic value. Kaplan-Meier survival analysis revealed that patients in low BEX4 expression group had a worse prognosis than those with high BEX4 expression ( P  = .009). Multivariate analysis showed that BEX4 is an independent risk factor for overall survival both in TCGA and GSE62254 ( P  = .0142, .013, respectively). GSEA identified that the expression of BEX4 was related to DNA replication, RNA polymerase, cell cycle, and P53 signaling pathway. Conclusion: BEX4 is expressed at low levels in GC. BEX4 expression independently predicted poor OS for GC. It is a promising independent molecular predictor for the diagnosis and prognosis of GC.